Grupo pequeño de personas en un reunión. (UNED, 2023)
Aparece de pie Marina Volio Brenes, Francisco Antonio Pacheco Fernández -Rector, Ronald García Soto, Chester Zelaya Goodman, Eugenio Rodriguez Vega, junto a otras personas